2006
DOI: 10.1007/s00535-006-1820-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical features of recurrent acute pancreatitis in China

Abstract: Recurrent acute pancreatitis remains a frequent disease, with cholelithiasis and alcohol being the most usual etiological factors. Alcohol is the primary etiological factor in male patients. In about 26.8% of cases, the etiology remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
36
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
9
36
3
Order By: Relevance
“…About 2-10% of patients succumb to the initial illness [2] and another 10-35% go on to have recurrent episodes of acute pancreatitis [3][4][5]. Considering the potential burden of recurrent acute pancreatitis (RAP), it is surprising that there are few comprehensive articles on this entity [3][4][5]. Most papers deal with an etiological and/or therapeutic subset of RAP [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…About 2-10% of patients succumb to the initial illness [2] and another 10-35% go on to have recurrent episodes of acute pancreatitis [3][4][5]. Considering the potential burden of recurrent acute pancreatitis (RAP), it is surprising that there are few comprehensive articles on this entity [3][4][5]. Most papers deal with an etiological and/or therapeutic subset of RAP [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the true incidence and aetiology of RAP in the idiopathic group are not clear from these studies as the commonest causes of RAP in these series were alcohol intake and gallstones. [10][11][12] Patients with gallstones undergo cholecystectomy and thus there is no further risk of recurrence in the majority of patients while patients who continue to consume alcohol usually develop CP. In general, as the known causes of AP are taken care of, RAP usually occurs in the idiopathic group.…”
Section: Recurrent Acute Pancreatitis (Rap)mentioning
confidence: 99%
“…According to Gao-YanJing et al, 2 its frequency is much lower in China (10.7%) than in Europe (27%). The Chinese percentage reported by Gao-YanJing et al 2 is also much lower than has generally been reported in the past (from 30% to 60%). [3][4][5][6][7][8][9][10] Although this difference in frequency may derive from racial differences, differences in the distribution in etiologies may contribute.…”
mentioning
confidence: 47%
“…In this issue of Journal of Gastroenterology, GaoYanJing et al 2 reported the recent clinical proflle of recurrent acute pancreatitis in China. This paper is the exact Chinese counterpart to the European report by Gullo et al, 3 and we can easily compare the differences in the clinical presentation of recurrent acute pancreatitis between China and Europe.…”
mentioning
confidence: 98%